2016
DOI: 10.18632/oncotarget.11128
|View full text |Cite
|
Sign up to set email alerts
|

The gain and loss of long noncoding RNA associated-competing endogenous RNAs in prostate cancer

Abstract: Prostate cancer (PC) is one of the most common solid tumors in men. However, the molecular mechanism of PC remains unclear. Numerous studies have demonstrated that long noncoding RNA (lncRNA) can act as microRNA (miRNA) sponge, one type of competing endogenous RNAs (ceRNAs), which offers a novel viewpoint to elucidate the mechanisms of PC. Here, we proposed an integrative systems biology approach to infer the gain and loss of ceRNAs in PC. First, we re-annotated exon microarray data to obtain lncRNA expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…In addition, in our study, HOTAIR overexpression was found to be positively correlated with advanced histological grade, FIGO stage and extensive metastasis, indicating that HOTAIR was an excellent biomarker for the prognosis of ovarian cancer and that the downregulation of HOTAIR may arrest tumor progression and inhibit the metastatic phenotype. Currently, the lncRNA-miRNA-mRNA regulatory network is widely recognized; in this network, lncRNA acts as a natural miRNA sponge (ceRNA) to sponge miRNAs, thus decreasing the expression of miRNA targets and affecting posttranscriptional regulation [32]. For example, it is reported that lncRNA PTENP1 functioned as a ceRNA to modulate PTEN levels by decoying miR-106b and miR-93 in gastric cancer [33].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…In addition, in our study, HOTAIR overexpression was found to be positively correlated with advanced histological grade, FIGO stage and extensive metastasis, indicating that HOTAIR was an excellent biomarker for the prognosis of ovarian cancer and that the downregulation of HOTAIR may arrest tumor progression and inhibit the metastatic phenotype. Currently, the lncRNA-miRNA-mRNA regulatory network is widely recognized; in this network, lncRNA acts as a natural miRNA sponge (ceRNA) to sponge miRNAs, thus decreasing the expression of miRNA targets and affecting posttranscriptional regulation [32]. For example, it is reported that lncRNA PTENP1 functioned as a ceRNA to modulate PTEN levels by decoying miR-106b and miR-93 in gastric cancer [33].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Recent studies verified that miRNAs was useful for lncRNA analysis [ 52 54 ]. For example, lncRNAs could act as miRNA sponges to regulate the expression of other transcripts [ 55 ]. In order to evaluate the ceRNA interactions that were mediated by lncRNAs, we constructed the lncRNA-miRNA-mRNA ceRNA network through a multi-step method ( Supplementary Figure S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, functional genomic analyses were designed to provide a potential biological basis for the observed associations. Rs10132552 polymorphisms could create miRNA (mir-564, mir-650 and mir-602) binding sites on MEG3 , disturbing the lncRNA-miRNA interaction, acting as competing endogenous RNAs (ceRNA) and thereby negatively regulating miRNA expression 36 , 37 . Interestingly, it is clear that mir-650, mir-602 and mir-564 played roles in cancers such as breast cancer and lung cancer 38 40 .…”
Section: Discussionmentioning
confidence: 99%